Effective interventions for potentially modifiable dementia risk factors: Their costs and cost‐effectiveness: Health services research: Cost of care and implications for intervention. (7th December 2020) - Mukadam, Naaheed; Anderson, Robert; Knapp, Martin Richard John; Wittenberg, Raphael; Karagiannidou, Maria; Gonzales, Sergi Costafreda; Tutton, Madison; Alessi, Charles; Livingston, Gill
Abstract: Background: The potential economic value of interventions to prevent dementia is unknown. We modelled this for potentially modifiable dementia risk factors. Method: We searched PubMed and Web of Science from inception to July 2018 and included interventions that (a) successfully targeted any of nine pre‐specified potentially modifiable risk factors (hypertension, diabetes, hearing loss, obesity, physical inactivity, social isolation, depression, cigarette smoking and less childhood education), (b) had robust evidence that the intervention improved risk or risk behaviour and (c) are feasible in an adult population. We established when in the life‐course each intervention would be delivered. We calculated dementia incidence reduction from: annual incidence of dementia in people with each risk factor; population attributable fraction for each risk, corrected for risk factor clustering, and how effectively the intervention controls the risk factor. We calculated the discounted value of lifetime health gain (including reduced dementia mortality) and impact on cost (including NHS, social care and carer costs) per person eligible for treatment. We estimated annual total expenditure on the fully operational intervention programme in England. Result: We found effective treatments for hypertension, stopping smoking, diabetes prevention and hearing loss. Treatments for stopping smoking and provision of hearing aids reduced cost. Treatment of hypertension was cost‐effective by reference to standard UK thresholds. The three interventions when fully implemented would save £1·863 billion annually in England, reduce dementia prevalence by 8·5% and produce QALY gains. The intervention for diabetes was unlikely to be cost‐effective in terms of impact on dementia alone. Conclusion: There is a strong case for implementing the three effective interventions on grounds of cost‐effectiveness and quality of life gains, as well as for improvements in general health. While some people will decline or discontinue interventions, there is considerable room for the interventions to remain cost‐saving or cost‐effective even if adherence is lower.